Two extensional events in the early evolution of the Yangtze Block, South China: Geochemical and isotopic evidence from two sets of Paleoproterozoic alkali porphyry in the Northern Kongling terrane. (10th March 2020) - Li, Haiquan; Zhou, Wenxiao; Wei, Yunxu; Chang, Feng; Wang, Bo; Tan, Mantang; Hu, Zhengxiang; Xu, Daliang; Liu, Hao
Abstract : A set of granite porphyry (grnt‐porphyry) and sub‐rhyolite porphyry (rhy‐porphyry) with specific blue quartz phenocrysts was disintegrated in the northern Kongling terrane, China. Geochemical and isotopic analyses were performed on samples from Kongziqiao (KZQ) and Baizhuping (BZP). In terms of major elements, both are rich in silicon and alkalis, but depleted in calcium and magnesium. Their trace element contents are also similar, exhibiting negative anomalies for large‐ion lithophile elements (LILEs) such as K, Rb and Sr but positive anomalies for high‐field‐strength elements (HFSEs) such as Hf, Ce and Lu. Other elements such as Nb, Ti, P, Sm, Ho, Y and Yb show negative anomalies; however, the KZQ grnt‐porphyry is characterized by positive Ba and negative Zr anomalies; whereas the BZP sub rhy‐porphyry has negative Ba, U and Ta anomalies. The overall geochemistry is characteristic of A‐type granite formed in an extensional environment (A2 ‐type). Yield ages of the KZQ grnt‐porphyry are (2, 239 Ma) and that of the BZP (1, 895 Ma) sub rhy‐porphyry are Paleoproterozoic. Analysis of Hf isotopes shows that both have negative ε Hf (t) values, but the εHf (t) value of the KZQ grnt‐porphyry is slightly more positive (minimum −12.4; mean − 8.8) and its depleted mantle model age (TDM1 = 2.85–3.06 Ga, mean 2.92 Ga) is slightly older than the BZP sub rhy‐porphyry (minimum ε Hf (t) = −17.1, mean − 14.9; TDM1 = 2.79–2.92 Ga, mean 2.85 Ga). This suggests that they are derived from partial melting of different generations of ancient crustal material, which implies significant stratification in the Archean crust. The ε Nd (t) values of two samples of each rock type also indicate that both were derived from Ca. 2.9 Ga ancient crust (εNd (t) KZQ = −5.58, −4.74; εNd (t)BZP = −8.55, −8.22). The petrogenesis of both rock types is related to deep crustal extensional collapse caused by post‐orogenic extension before 2.2 Ga and after 1.9 Ga. The formation of two porphyries represents the changes in tectonic system of the Yangtze Block, and this tectonic evolution may have contributed to the reconstruction of the Columbia supercontinent.